2000
DOI: 10.1006/dbio.2000.9935
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Stem Cells and Transgenic Mice Ubiquitously Expressing a Tau-Tagged Green Fluorescent Protein

Abstract: We have generated embryonic stem (ES) cells and transgenic mice carrying a tau-tagged green fluorescent protein (GFP) transgene under the control of a powerful promoter active in all cell types including those of the central nervous system. GFP requires no substrate and can be detected in fixed or living cells so is an attractive genetic marker. Tau-tagged GFP labels subcellular structures, including axons and the mitotic machinery, by binding the GFP to microtubules. This allows cell morphology to be visualiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 32 publications
2
112
0
Order By: Relevance
“…B6 mice (The Jackson Laboratory, Bar Harbor, ME) were used for most experiments. In addition, reeler mice (B6C3Fe a/a-Reln rl /J; The Jackson Laboratory), tau-GFP transgenic mice (Pratt et al, 2000), and Math1 mutant mice (Math1 lacZ and Math1 Ϫ ) (Wang et al, 2005) were used for some experiments where indicated. The mice were used according to a protocol approved by the Institutional Animal Care and Use Committee at the University of Washington.…”
Section: Methodsmentioning
confidence: 99%
“…B6 mice (The Jackson Laboratory, Bar Harbor, ME) were used for most experiments. In addition, reeler mice (B6C3Fe a/a-Reln rl /J; The Jackson Laboratory), tau-GFP transgenic mice (Pratt et al, 2000), and Math1 mutant mice (Math1 lacZ and Math1 Ϫ ) (Wang et al, 2005) were used for some experiments where indicated. The mice were used according to a protocol approved by the Institutional Animal Care and Use Committee at the University of Washington.…”
Section: Methodsmentioning
confidence: 99%
“…For each marker and each stage, three to five nonexencephalic embryos were analyzed at rostral, medial, and caudal levels of the developing forebrain. Golli-GFP (Jacobs et al, 2007) and GFP mice (Pratt et al, 2000) were bred into the Pdn line.…”
Section: Methodsmentioning
confidence: 99%
“…p16 and pl6 P114L were cloned as XhoI fragments into pCAGiP (Pratt et al, 2000), such that their expression was under the control of the CAG promoter. A measure of 10-20 mg of ScaI-linearized pCAG.p16 and pCAG.p16 Pll4L DNA was electroporated into ES cells (3-5 Â 10 7 cells) using a BioRad Gene Pulser (200 V, 500 mF).…”
Section: Stable Expression Of P16 Ink4a In Es Cellsmentioning
confidence: 99%